A lithiation/delithiation mechanism of monodispersed MSn5 (M = Fe, Co and FeCo) nanospheres1. Issue 13 (7th April 2015) - Xin, Fengxia; Wang, Xiaoliang; Bai, Jianming; Wen, Wen; Tian, Huajun; Wang, Chunsheng; Han, Weiqiang
<x xml:space="preserve">Abstract</x> The same crystal structure, identical particle surface morphology and the similar particle size distribution of MSn5 (M = Fe, Co and FeCo) phases are ideal for comparison of the electrochemical performance, reaction mechanism, thermodynamics and kinetics.